THE ANALYSIS OF WULUH STARFRUIT LEAF EXTRACT (Averrhoa blimbi Linn) AS INHIBITOR ON CORROSION RATE OF STAINLESS STEEL ORTHODONTIC WIRE - Larasitae G Banjang; Diana Wibowo; Fajar Kusuma Dwi Kurniawan (FKG Unlam, 2018)
Background: One type of wire used in orthodontic treatment is stainless steel and it has a potential to corrosion due to the environment around the oral cavity. The corrosion rate may happens depends the effect from the environment around the metal. One of the method that can be done to lower the corrosion rate is by using the extract of wuluh starfruit leaf (Averrhoa bilimbi Linn) as an organic inhibitor. Purpose: The purpose of this research is to analyze the extract of wuluh starfruit leaf in lowering the corrosion rate of orthodontic stainless steel wire. Methods: This research was included as a kind of true experimental with post-test only control group design. This research consisted of control group and two treatment groups. Each group consisted of 10 sample orthodontic stainless steel wire with a length of 5 cm which was cut and scraped along the wire, then measured the corrosion rate on groups immersion in saline solution and the extract of wuluh starfruit leaf. Results: The results of this research showed that the average rate of corrosion ortodonthic stainless steel wire immersed in the wuluh starfruit leaf extract with concentration 1000 ppm was equal to 3,24x10-5 mm/y. The average rate of corrosion immersed in the wuluh starfruit leaf extract with concentration 600 ppm was equal to 6,31x10-5 mm/y and the average rate of corrosion immersed in a solution of saline was equal to 1,34x10-4 mm/y. Conclusion: The wuluh starfruit leaf extract can lower the corrosion rate which is indicated by the highest corrosion reduction in the group a wuluh starfruit leaf extract with concentration 1000 ppm.